High Energy Processes in Protostellar Jets - Rodríguez Kamenetzky, Adriana (2015)
In the last years the presence of synchrotron emission has been proposed in a handful of protostellar jets. However, it is yet unclear how this "slow" jets could be able to accelerate particles up to relativistic velocities in order to emit detectable synchrotron emission. One of the most likely possibilities is that particles are accelerated in strong shocks of the jet against the dense envelopes surrounding the protostar. Particle acceleration has been studied in several astrophysical systems (AGN’s, microquasars, SN, massive binaries, etc.), nevertheless, in YSO is a fairly new phenomenon. Here, we present the analysis of high sensitivity continuum and linearly polarized images at several frequencies of one of the most characteristic non-thermal protostellar jets: The Triple Radio Source in Serpens.